Lifestyle-based oxidative balance score and its association with cardiometabolic health of the community-dwelling elderly: A cross-sectional secondary analysis - Li, Yang; Yuan, Huixiao; Li, Qingqing; Geng, Shasha; Chen, Xin; Zhu, Yingqian; Jiang, Hua (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiometabolic diseases, the main disease burden in older adults, are largely caused by oxidative stress resulting from lifestyle factors. This study investigated the relationship between lifestyle-based oxidative balance scores and cardiometabolic health among the community-dwelling elderly. Methods This work conducted a secondary analysis of previous cross-sectional research data and constructed a lifestyle-based oxidative balance score (LOBS) including 4 components (higher scores were considered more antioxidant). Linear regression models and logistic regression models were used to evaluate the associations with cardiometabolic biomarkers and the number of cardiometabolic risk factors. Besides, we investigated whether these associations differed by covariates. Results A total of 710 individuals (60.99% female, median age 70.0 years) were recruited. The inverse associations of LOBS with SBP and TG and the positive association with HDLC were statistically significant in both linear and logistic regression models. In contrast, an inverse association of LOBS with DBP was significant only in the linear regression model (all P < 0.05). The associations of LOBS with TG and HDLC were not affected by age, gender, or socioeconomic level. A significant inverse association was observed between LOBS and the number of cardiometabolic risk factors. Compared with the lowest LOBS, the ORs for more cardiometabolic risk factors in the second and third intervals were 0.577 (0.422, 0.788) and 0.460 (0.301, 0.703) (both P<0.001). Conclusion In summary, this study shows that antioxidant-predominant lifestyle exposure yields a better cardiometabolic health status. We recommend that general practitioners should offer comprehensive healthy lifestyle management to community-dwelling elderly.